Latent tuberculosis infection associates with cardiac involvement in patients with sarcoidosis - Beijer, Els; Bakker, Annelies; Kraaijvanger, Raisa; Meek, Bob; Post, Marco C.; Grutters, Jan C.; Veltkamp, Marcel (Sarcoidosis, Vasculitis and Diffuse Lung Diseases, 2020)
Background: Sarcoidosis is a systemic disease characterized by formation of non-caseating granulomas. About 5% of patients have symptoms of cardiac sarcoidosis. Identification of cardiac involvement is important since it is a major cause of death. Mycobacterial antigens have been linked to sarcoidosis pathogenesis. Previous findings suggest that a latent tuberculosis infection (LTBI) might associate with development of cardiac involvement in patients with sarcoidosis. The aim of the present study was to further evaluate these findings in another cohort of cardiac sarcoidosis patients. Methods: Interferon release assays (IGRAs) or tuberculin skin tests (TSTs) were analysed in a cohort of cardiac sarcoidosis patients (n=103) and compared to non-cardiac sarcoidosis patients (n=153). Results: In the cohort of patients with cardiac sarcoidosis, 7 could be diagnosed with a LTBI (6.8%) compared to only one of the non-cardiac patients (0.7%), p = 0.008. Conclusions: To conclude, we were able to show an association between a LTBI and cardiac involvement in patients with sarcoidosis. Future research is however required to unravel the mechanism involved in this association.